Semi-field studies on biochemical markers of honey bee workers (Apis mellifera) after exposure to pesticides and their mixtures. - Agnieszka Murawska; Ewelina Berbeć; Krzysztof Latarowski; Adam Roman; Paweł Migdał (PLoS ONE)
Due to the fact that many different pesticides are used in crop production and their residues can accumulate in the environment, bees are in contact with various pesticides at the same time. Most studies on their influence on honey bees focus on single substances in concentrations higher than those found in the environment. Our study assessed the chronic effects of commonly used pesticides and their mixtures on selected biochemical markers in worker bee hemolymph. Workers developed in the hive and were provisioned with to pesticides in concentrations corresponding to residues detected in pollen, honey, and/or nectar. Colonies were exposed daily to 0.5L for 7 days by feeding a sugar syrup containing a formulation of acetamiprid (250 ppb) (insecticide), glyphosate (7200 ppb) (herbicide), and tebuconazole (147 ppb) (fungicide) administered alone, in a binary or ternary mixture. Administered alone, acetamiprid significantly decreased the level of urea in the hemolymph of worker honey bees. Glyphosate did not affect significantly the level/activity of any of the biochemical markers. Tebuconazole caused changes in the levels of most of the studied biochemical markers. We found that tebuconazole, which as a fungicide is generally considered safe for bees, may be harmful and more research is required. The impact of fungicides is a crucial element of the assessment of threats to honey bees.